The United States and the Second World War : the European revolution and tasks of the revolutionary party : resolutions of eleventh convention of the American Trotskyist Movement. - Socialist Workers Party of United States (SWP) (New York : Pioneer Publishers, 1945)
Bibliotheek François Vercammen
Engels
Brochure
Keywords: trotskisme; Verenigde Staten